2020
DOI: 10.3390/nu12082309
|View full text |Cite
|
Sign up to set email alerts
|

“It’s Important but, on What Level?”: Healthy Cooking Meanings and Barriers to Healthy Eating among University Students

Abstract: The negative impact of a sedentary lifestyle and poor diet on health is evident across the lifespan, but particularly during the university period. Usually, the diet of university students is rich in sweetened drinks and processed foods and low in fruits, vegetables and legumes. Although there is an association between maintaining a healthy diet and the frequency of cooking at home, the time currently spent on cooking or learning how to cook is decreasing globally. The main aim of this study was to explore uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 40 publications
0
17
0
5
Order By: Relevance
“…The possible barriers that were stated in other studies, such as inconvenience, lack of time, and financial reasons [ 4 , 8 , 9 , 11 ], did not have a significant relationship with decreased healthy habits, although not knowing how to plan a diet did (β = −0.180, p = 0.025). This was against expectations, as studies have found that the UAE population chooses unhealthy options because they are more convenient, cheaper, and more accessible [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The possible barriers that were stated in other studies, such as inconvenience, lack of time, and financial reasons [ 4 , 8 , 9 , 11 ], did not have a significant relationship with decreased healthy habits, although not knowing how to plan a diet did (β = −0.180, p = 0.025). This was against expectations, as studies have found that the UAE population chooses unhealthy options because they are more convenient, cheaper, and more accessible [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 67%
“…They indicated their belief that cooking a healthy meal is time-consuming, requires more effort, and costs more than buying fast food or ready-to-eat food. Students also commented that unhealthy and processed food was easily accessible on their university campus, through vending machines or stores [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to dietary habits, university is the time when previously learned patterns can be cemented, or new patterns can be learned and replace old ones [ 17 , 18 ]. Many variables can exert influence on the ways that university students nourish themselves, including individual factors (e.g., the lack of self-discipline or time constraints), support networks (e.g., the influence of peers or the lack of parental monitoring), the local environment (e.g., accessibility or the appeal and price of certain food products) as well as the macro environment (e.g., advertising) [ 19 , 20 ]. Other sociodemographic variables have also been connected to the DQ of university students, including the following: living alone [ 21 ], gender [ 22 ], satisfaction with one’s studies and academic performance [ 23 ], lack of information [ 24 ] as well as anxiety and depression [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…University students perceive time constraints as a barrier to implementing healthy eating behaviors [ 22 ]. If they perceive it as being difficult to dedicate time to healthy eating at the same time as, for example, attending classes [ 47 ], it is understandable that they also do not attach much importance to the social gathering around food in their daily lives. in any case, none of these studies have made an empirical observation based on the life experience of the target population [ 46 ] but have rather relied on experts for the development of the scale or followed nutritional recommendations from the country, or based on previous research [ 44 , 48 ].…”
Section: Discussionmentioning
confidence: 99%